2012
DOI: 10.1016/j.urolonc.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Germline prognostic markers for urinary bladder cancer: Obstacles and opportunities

Abstract: Urinary bladder cancer is a heterogeneous disease with diverse genetic and environmental risk factors that can influence disease risk or clinical course for recurrence, progression, and survival. Therefore, identification of these factors is paramount for disease prevention and optimal clinical management of bladder cancer patients. Of particular interest is the need to identify molecular biomarkers that can give accurate assessment of tumor biological potential and to predict treatment response. Recent advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…2 Prognostic biomarkers are vital for the accurate prediction of outcome and to determine which patients need more aggressive postoperative intervention. [25][26][27] PCDH8 methylation was present in a high proportion of bladder cancer tissues in the present study, and was associated with malignant behaviour. PCDH8 promoter methylation may therefore represent a useful prognostic biomarker in bladder cancer.…”
Section: Discussionsupporting
confidence: 53%
“…2 Prognostic biomarkers are vital for the accurate prediction of outcome and to determine which patients need more aggressive postoperative intervention. [25][26][27] PCDH8 methylation was present in a high proportion of bladder cancer tissues in the present study, and was associated with malignant behaviour. PCDH8 promoter methylation may therefore represent a useful prognostic biomarker in bladder cancer.…”
Section: Discussionsupporting
confidence: 53%
“…In the past, many inherited genetic variants were reported to be associated with bladder cancer risk using a candidate‐gene approach. However, few of these candidate‐gene associations has been consistently replicated (Chang et al, ). In , Kiemeney et al conducted the first genome‐wide association study (GWAS) of urinary bladder cancer in a European population and identified two single‐nucleotide polymorphisms (SNPs) that were significantly associated with bladder cancer risk (Kiemeney et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the contribution of genetic variation in determining bladder cancer risk [18]. In recent years, GWAS have emerged as a powerful approach in the discovery of genetics underlying complex traits like cancer.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%